Booster dose of SARS-CoV-2 messenger RNA vaccines strengthens the specific immune response of patients with rheumatoid arthritis: A prospective multicenter longitudinal study - Farroni, Chiara; Aiello, Alessandra; Picchianti-Diamanti, Andrea; Laganà, Bruno; Petruccioli, Elisa; Agrati, Chiara; Garbuglia, Anna Rosa; Meschi, Silvia; Lapa, Daniele; Cuzzi, Gilda; Petrone, Linda; Vanini, Valentina; et al. (International journal of infectious diseases, 2022)
•After receiving a COVID-19 booster, the antibody response increases in controls and rheumatoid arthritis (RA)-patients.•After the booster, interferon-γ release assay-specific response remains stable in RA.•After the booster, the spike-specific response is clusters of differentiation (CD)4-driven in health care workers and patients with RA.•In RA, the booster is associated with low spike-CD4 response and interleukin-2 impairment. To characterize the kinetics of humoral and T-cell responses in rheumatoid arthritis (RA)-patients followed up to 4-6 weeks (T3) after the SARS-CoV-2 vaccine booster dose. Health care workers (HCWs, n = 38) and patients with RA (n = 52) completing the messenger RNA vaccination schedule were enrolled at T3. In each cohort, 25 subjects were sampled after 5 weeks (T1) and 6 months (T2) from the first vaccine dose. The humoral response was assessed by measuring anti-receptor-binding domain (RBD) and neutralizing antibodies, the T-cell response by interferon-γ-release assay (IGRA), T cell cytokine production, and B cell phenotype at T3 by flow cytometry. Patients with RA showed a significant reduction of antibody titers from T1 to T2 and a significant increase at T3. T-cell response by IGRA persisted over time in patients with RA, whereas it increased in HCWs. Most patients with RA scored positive for anti-RBD, neutralizing antibody and T-cell responses, although the magnitude was lower than HCWs. The spike-specific-cytokine response was mainly clusters of differentiation (CD)4+ T cells restricted in both cohorts and significantly lower with reduced interleukin-2 response and CD4-antigen-responding naïve T cells in patients with RA. Unswitched memory B cells were reduced in patients with RA compared with HCWs independently of vaccination. COVID-19 vaccine booster strengthens the humoral immunity in patients with RA even with a reduced cytokine response.